Effects of anonymity on decision making and evaluations of others' decisions in moral dilemmas - Hitoshi Terai; Shinji Kai; Misato Oi (Acta Psychologica)
This study aimed to examine the effects of anonymity on decision making and evaluations of others' decisions in moral dilemmas. The following three conditions were examined: the use of one's real name, pseudonymity (i.e., the use of a nickname), and complete anonymity. Participants made decisions and evaluated others' decisions in the trolley and footbridge problems. The results indicated that during decision making, anonymity increased participants' preference for utilitarian decisions. This suggests that anonymity might diminish empathy, leading to a greater inclination toward utilitarian decisions. Conversely, during evaluations of others' decisions, anonymity generally made participants more accepting of nonutilitarian decisions and less accepting of utilitarian ones. These findings suggest that anonymity might facilitate more intuition-oriented evaluations in the process of evaluating decisions. These effects were not observed for pseudonymity, and their significance is discussed.